Perceptions of cardiac rehabilitation patients, specialists and rehabilitation programs regarding cardiac rehabilitation wait times - Grace Sherry L; Tan Yongyao; Marcus Louise; Dafoe William; Simpson Chris; Suskin Neville; Chessex Caroline (BMC, 2012)
Abstract Background In 2006, the Canadian Cardiovascular Society (CCS) Access to Care Working Group recommended a 30-day wait time benchmark for cardiac rehabilitation (CR). The objectives of the current study were to: (1) describe cardiac patient perceptions of actual and ideal CR wait times, (2) describe and compare cardiac specialist and CR program perceptions of wait times, as well as whether the recommendations are appropriate and feasible, and (3) investigate actual wait times and factors that CR programs perceive to affect these wait times. Methods Postal and online surveys to assess perceptions of CR wait times were administered to CR enrollees at intake into 1 of 8 programs, all CCS member cardiac specialists treating patients indicated for CR, and all CR programs listed in Canadian directories. Actual wait times were ascertained from the Canadian Cardiac Rehabilitation Registry. The design was cross-sectional. Responses were described and compared. Results Responses were received from 163 CR enrollees, 71 cardiac specialists (9.3% response rate), and 92 CR programs (61.7% response rate). Patients reported that their wait time from hospital discharge to CR initiation was 65.6 ± 88.4 days (median, 42 days), while their ideal median wait time was 28 days. Most patients (91.5%) considered their wait to be acceptable, but ideal wait times varied significantly by the type of cardiac indication for CR. There were significant differences between specialist and program perceptions of the appropriate number of days to wait by most indications, with CR programs perceiving shorter waits as appropriate (p < 0.05). CR programs reported that feasible wait times were significantly longer than what was appropriate for all indications (p < 0.05). They perceived that patient travel and staff capacity were the main factors negatively affecting waits. The median wait time from referral to program initiation was 64 days (mean, 80.0 ± 62.8 days), with no difference in wait by indication. Conclusions Wait times following access to cardiac rehabilitation are prolonged compared with consensus recommendations, and yet are generally acceptable to most patients. Wait times following percutaneous coronary intervention in particular may need to be shortened. Future research is required to provide an evidence base for wait time benchmarks.